The use of autologous biomaterials in combination with biocompatible matrices for restoration of bone tissue defects (literature review) - D. V. Bulgin; I. S. Bazarov; V. V. Khominets; A. L. Kovtun; D. A. Ivanov; E. Yu. Radomskaya; A. A. Shiryaev; D. A. Zaichikov (Вестник трансплантологии и искусственных органов)
Bone defect repair is an interdisciplinary research field encompassing surgical orthopedics, regenerative medici- ne, tissue engineering, immunology (addressing biocompatibility challenges), materials science and technology (including additive manufacturing, porosity, and mechanical strength), and nanotechnology for developing bio- compatible matrices that enhance bone regeneration. This literature review highlights recent advancements in bone tissue engineering, focusing on the application of autologous biomaterials in combination with biocompatible matrices to improve bone regeneration outcomes.